Human clinical trial using diagnostic ultrasound and microbubbles to enhance neoadjuvant chemotherapy in HER2- negative breast cancer - Zhou, Biqiang; Lian, Qingshu; Jin, Chunchun; Lu, Jianghao; Xu, Lifeng; Gong, Xuehao; Zhou, Peng (Frontiers in Oncology, 2022)
Background: In vivo and in vitro experiments have demonstrated that diagnostic ultrasound combined with microbubbles (USMB) can enhance tumor chemotherapy, but few clinical studies have explored the effect of USMB in human HER2-negative breast cancer. We aimed to compare USMB combined with neoadjuvant chemotherapy (NAC) with NAC alone in the treatment of human HER2-negative breast cancer. Methods: Patients (n=10) enrolled in the study were treated with TAC (taxane – (docetaxel), anthracycline – (epirubicin or doxorubicin liposomes), and cyclophosphamide) and ultrasound using a commercial clinical ultrasound scanner for 20 min after each chemotherapy session, followed by intermittent injections of SonoVue® to induce sonoporation and enhance therapeutic efficacy. Contrast-enhanced ultrasound (CEUS) was used to record tumor perfusion before and after ultrasound treatment. Results: After completion of chemotherapy, the maximum tumor diameter of patients in the combined treatment group (n=10) was significantly smaller than that in the control group (n=16) (p=0.017). Although the combined treatment group had higher overall response and clinical benefit rates than those in the control group, there was no statistically significant difference in RECIST between the combined treatment group and the control groups (p=0.590). More patients in the combination therapy group achieved pathologic complete response than in the control group (p=0.014). For combined treatment, CEUS revealed that the peak intensity, mean transit time, and area under the curve were higher after treatment than before treatment (p<0.001, p<0.001, p=0.003, respectively). Combined therapy did not cause additional toxicity or increase side effects Conclusion: USMB and chemotherapy can be combined in a clinical setting using commercially available equipment, without additional toxicity, and may improve the efficacy of NAC in HER2-negative breast cancer.